Structure and metabolic function of spatiotemporal pit mud microbiome - Zhihua Li; Chi Zhao; Zhenyu Mao; Fengju Zhang; Ling Dong; Chuan Song; Yao Chen; Xin Fu; Zonghua Ao; Yanfei Xiong; Qin Hui; Weizhi Song; et al. (Environmental Microbiome)
Abstract Background Pit mud (PM) hosts diverse microbial communities, which serve as a medium to impart flavor and quality to Baijiu and exhibit long-term tolerance to ethanol and acids, resulting in a unique ecosystem. However, the ecology and metabolic functions of PM remain poorly understood, as many taxa in PM represent largely novel lineages. In this study, we used a combination of metagenomic analysis and chemical derivatization LC–MS analysis to provide a comprehensive overview of microbial community structure, metabolic function, phylogeny, horizontal gene transfer, and the relationship with carboxyl compounds in spatiotemporal PM samples. Results Our findings revealed three distinct stages in the spatiotemporal changes of prokaryotic communities in PM: an initial phase dominated by Lactobacillus, a transitional phase, and a final state of equilibrium. Significant variations in α- and β-diversity were observed across different spatial and temporal PM samples. We identified 178 medium- and high-quality non-redundant metagenome-assembled genomes (MAGs), and constructed their phylogenetic tree, depicting their roles in the carbon, nitrogen, and sulfur cycles. The Wood-Ljungdahl pathway and reverse TCA cycle were identified as the main carbon fixation mechanisms, with both hydrogenotrophic and aceticlastic methanogens playing a major role in methane production, and methylotrophic pathway observed in older PM. Furthermore, we identified relationships between prokaryotes and 29 carboxyl metabolites, including medium- and long-chain fatty acids. Horizontal gene transfer (HGT) was widespread in PM, particularly among clostridia, Bacteroidota, Bacilli, and Euryarchaeota, and was shown to play critical roles in fermentation dynamics, carbon fixation, methane production, and nitrogen and sulfur metabolism. Conclusion Our study provides new insights into the evolution and function of spatiotemporal PM, as well as its interactions with carboxyl metabolites. Lactobacillus dominated in new PM, while methanogens and clostridia were predominant in older or deeper PM layers. The three distinct stages of prokaryotic community development in PM and HGT played critical roles in metabolic function of spatiotemporal PM. Furthermore, this study highlights the importance of α-diversity, β-diversity, methanogens, and Clostridium as useful indicators for assessing PM quality in the production of high-quality Baijiu.